2021
DOI: 10.3357/amhp.5798.2021
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue, Emotion, and Cognitive Performance in Simulated Long-Duration, Single-Piloted Flight Missions

Abstract: BACKGROUND: Fatigue of air force pilots has become an increasing concern due to changes in mission characteristics. In the current study we investigated fatigue, emotions, and cognitive performance in a simulated 11-h mission in the 39 Gripen fighter aircraft. METHODS: A total of 12 subjects were evaluated in a high-fidelity dynamic flight simulator for 12 consecutive hours. Perceived fatigue was measured by the Samn-Perelli Fatigue Index (SPFI). Emotions were assessed with the Circumplex Affect Space. Cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Regarding emotions, nevertheless, these results are in line with previous findings over time in these environmental conditions (Rosa et al, 2021 ), where emotionality ratings addressing glad/cheerful significantly decreased after approximately 7 hours into the mission. Similarly, emotions addressing drowsy/bored significantly increased after 7 hours and, following the same trend, participants reported being less active/stimulated and more passive/inactive, also after around hour 7.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Regarding emotions, nevertheless, these results are in line with previous findings over time in these environmental conditions (Rosa et al, 2021 ), where emotionality ratings addressing glad/cheerful significantly decreased after approximately 7 hours into the mission. Similarly, emotions addressing drowsy/bored significantly increased after 7 hours and, following the same trend, participants reported being less active/stimulated and more passive/inactive, also after around hour 7.…”
Section: Discussionsupporting
confidence: 92%
“…Detailed results regarding fatigue, cognitive performance and emotions have been reported in other publications (Rosa et al, 2020 ; Rosa et al, 2021 ). Here, we briefly summarize the main findings from these studies.…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…Previous studies have found that pilots’ performance is influenced by cognitive fatigue [e.g., Dehais et al (2018 , 2019) , Keller et al (2019) , Rocha and Silva (2019) , Quental et al (2021) , and Rosa et al (2021) ]. Implementing pBCI or neuro-adaptive technology is a relevant approach to study cognitive fatigue and to improve flight safety ( Zander et al, 2016 ; Arico et al, 2017 ; Dehais et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%